Membina Generasi Sehat Mental dengan Sosialisasi Mental Health di SMPN 003 Desa Pantai Raja - Dian Oktary; Fany Aprilia; Fariza Rahmadayani; Rusdian Shabrina Mukti R; Syakhila Takhira; Tesa Sessio Mentiana; Viona Nursepti Triaswati; Yona Triwulandari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Adolescence is the most crucial, most complicated period in the development phase of human life. There are many phenomena that teenagers have problems with, which cannot be separated from the perspective of psychological problems, so that quite a few teenagers who are confused about managing their problems are affected by stress which leads to depression. Whatever problems teenagers experience cannot be separated from many factors, one of which is mental health. Mental health is defined as the fulfillment of mental functions that are able to make individuals productive, able to have healthy relationships with other people and able to overcome difficulties. The method of this service is lecture and discussion.The result of this service is providing outreach related to Fostering a Mentally Healthy Generation with Mental Health Socialization at SMPN 003 Pantai Raja Village. The conclusion from the service carried out by the Kukerta MBKM team can be explained that almost teenagers are confused about how to manage their mental health so that it remains in good condition. Teenagers in this generation are very vulnerable to mental health disorders. However, teenagers feel facilitated by this discussion study related to mental health so that teenagers feel enlightened and can have input in mental health management.